The Whitman revolution : sex, poetry, and politics - Erkkila, Betsy, 1944- (Iowa Whitman series., 2020)
"In this set of essays, Betsy Erkkila's daring, insights, and range as a Whitman scholar are evident. The Whitman Revolution brings together a rich collection of her phenomenally influential essays that have been published over the years, along with two powerful new additions. She offers a moving account of the inseparable mix of the spiritual-sexual-political in Whitman and the absolute centrality of male-male connection to his work and thinking. Indeed, Erkkila has been on the forefront of scholarship positing that Whitman's songs are songs not only of workers and occupations but of sex and the body, homoeroticism and liberation. What is more, Erkkila demonstrates that this sexuality and communal impulse is central to Whitman's revolutionary poetry and his conception of democracy itself-an insight that was all but suppressed during the mid-20th century emergence of American literature as a field of study. Highlights of the collection include her essays on pairings such as Marx and Whitman, Dickinson and Whitman, and Melville and Whitman. Across the volume, she demonstrates an international vision that highlights the place of Leaves of Grass within a global struggle for democracy. The Whitman Revolution is evidence of Erkkila's remarkable ability to lead critical discussions, and marks an exciting event in Whitman Studies"--